Mechanical and Thermal Properties of Rubber Toughened Poly(lactic Acid)/ Multiwalled Carbon Nanotubes Nanocomposite - Mohd Shaiful Zaidi, Mat Desa; Azman, Hasan; Agus, Arsad; Nor Nisa, Mohammad (2014)
The effect of core-shell rubber (CSR) as impact modifier for Poly(lactic acid)/multiwalled carbon nanotubes (PLA/CNT) nanocomposites was investigated. In this work, the nanocomposites were prepared by direct melt blending method in a counter-rotating twinscrew extruder. The contents of CSR were varied between 5 to 20 wt% while the content of carbon nanotubes (CNT) were kept at 5 phr. PLA/CSR blend with 5 wt% core-shell rubber loading was also prepared. The extruded samples were injection moulded into the desired test specimens for mechanical and thermal properties analysis. Results indicated that introduction of 5 wt% CSR into PLA/CNT was able to improve tensile strength and impact strength with 27 % and 13 % increment respectively but was followed by reduction in the stiffness of the nanocomposite. Subsequent addition of more CSR content leads to steady increase in the toughness of the nanocomposite. However, the enhancement of impact strength of the nanocomposite is accompanied by gradual decrease of the tensile strength and Young’s modulus as well as flexural properties. The highest impact strength was recorded at PLA nanocomposite with 20 wt% CSR which stands at 6.94 kJ/m2.